MACRO ECONOMIC ANALYSIS AND ACCOUNTING SIDE OF THE DEVELOPMENT OF THE INDONESIAN BUSINESS CYCLE FROM 1998-2022 - Richard Andrew; Nirdukita Ratnawati; Syafri Syafri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The business cycle is one of the concerns of every macroeconomic policy of a country. The government needs to observe and overcome economic fluctuations carefully so that there is no recession in the economy of a country fluctuations in the Indonesian economy in a business cycle always occurs, especially from the valley of the Indonesian recession that occurred in 1998. In 1998, there was an economic crisis in almost all countries. This condition is aggravated by the rush where all customers take the funds they have stored in the bank simultaneously so as to make the financial liquidity ratio of a bank to be disrupted eventually the economy of a country becomes destroyed because there is no creditor institution that can help the economic distress in the country.Indonesia's economy continued to improve after 1998 from 1999 to 2019 the Indonesian economy continued to increase and continued to reach its peak in the reign of President Joko Widodo, where Indonesia'S GDP enters the G20, where Indonesia itself enters the top 16 countries that have the largest gross domestic product (GDP) in the world. Indonesia's economic conditions experienced their worst track record again during the covid 19 pandemic. Efforts continue to be made by the government so that Indonesia escapes the brink of recession during the pandemic with monetary and fiscal policies that continue to be carried out. But the question is whether it is all effective or make Indonesia's macro economy, especially its business cycle continues to deteriorate?. The purpose of this study is to analyze and study the macroeconomic policies of the Government of Indonesia in a business cycle of the Indonesian state. The research method used is case studies and literature that can provide a complete description and similar to what is experienced by a country in a business cycle. The results showed that Indonesia's macroeconomic policy in overcoming the recession in 1998 and the Covid 19 pandemic in 2020-2021 was successful in terms of monetary and fiscal policies so that the Indonesian economy was last recorded in 2022 to strengthen by 5.4% compared to 2020 and continues to strengthen and inflation until now. Keywords: Macroeconomics, fluctuations, Gross Domestic Product (GDP), business cycle, inflation